FUNGSI MANAJEMEN DAKWAH DALAM KEGIATAN KEAGAMAAN DI PANTI ASUHAN NAHDIYAT KOTA MAKASSAR (Fakultas Dakwah dan Komunikasi, 2020)
Teaching the thought of Islam requires good management so that in the implementation process it can run well. Management itself is a very important process in running an organization. So, in the orphanage management functions, we should apply some planning, organizing, implementing, monitoring and evaluating so that everything that is done can go according to objectives and the goals. With the management functions, the activities of teaching Islam can be arranged systematically and without the management of Islamic teachings, especially in managing the religious abilities of children in the orphanage, it will not run effectively and efficiently. The purpose of this study was to determine the Application of Da'wah Management Functions in religious activities at the Nahdiyat Orphanage in Makassar City. To find out about the Opportunities and Challenges of Applying Da'wah Management Functions in religious activities at the Nahdiyat Orphanage in Makassar City.